Metrics for the Evaluation of the Southern Ocean in Coupled Climate Models and Earth System Models. Issue 5 (2nd May 2018) - Russell, Joellen L.; Kamenkovich, Igor; Bitz, Cecilia; Ferrari, Raffaele; Gille, Sarah T.; Goodman, Paul J.; Hallberg, Robert; Johnson, Kenneth; Khazmutdinova, Karina; Marinov, Irina; Mazloff, Matthew; Riser, Stephen; et al.
Abstract: The Southern Ocean is central to the global climate and the global carbon cycle, and to the climate's response to increasing levels of atmospheric greenhouse gases, as it ventilates a large fraction of the global ocean volume. Global coupled climate models and earth system models, however, vary widely in their simulations of the Southern Ocean and its role in, and response to, the ongoing anthropogenic trend. Due to the region's complex water‐mass structure and dynamics, Southern Ocean carbon and heat uptake depend on a combination of winds, eddies, mixing, buoyancy fluxes, and topography. Observationally based metrics are critical for discerning processes and mechanisms, and for validating and comparing climate and earth system models. New observations and understanding have allowed for progress in the creation of observationally based data/model metrics for the Southern Ocean. Metrics presented here provide a means to assess multiple simulations relative to the best available observations and observational products. Climate models that perform better according to these metrics also better simulate the uptake of heat and carbon by the Southern Ocean. This report is not strictly an intercomparison, but rather a distillation of key metrics that can reliably quantify the "accuracy" of a simulation against observed, or at least observable, quantities. One overall goal is to recommend standardization of observationally based benchmarks that the modeling community should aspire to meet in order to reduce uncertainties in climate projections, and especially uncertainties related to oceanic heat and carbon uptake. Plain Language Summary: Observationally based metrics are essential for the standardized evaluation of climate and earth system models, and for reducing the uncertainty associated with future projections by those models. Key Points: Observationally based metrics are essential for assessing, comparing, and improving the heat and carbon cycles in climate simulations Metrics included here assess winds and heat and carbon uptake, ACC transport, sea ice extent, frontal positions, and pH Ocean heat and carbon uptake are strongly correlated in models and observations